Understanding The Importance Of Application Of Love Accounting To Tax Reporting And Paying - wahyuni; Alimuddin; Amiruddin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to analyze how to uncover the importance of applying love accounting to tax reporting and payment (Case Study on CV. Citra Panca Mandiri). This type of research uses qualitative, with phenomenological approach. This research was conducted at the CV. Citra Panca Mandiri and Account Representative (AR) At KPP Madya Makassar, the informants consisted of 4 CPM staff, namely 3 people from the accounting division, 1 person from the tax division and 2 informants from KPP Madya Makassar. Data collection techniques used were interviews and documentation. The technique of data analysis consists of data reduction, data presentation, and conclusion. While checking the validity of data using triangulation of sources. Based on the results of data analysis, that it is very important to instill a sense of love in reporting and paying taxes, where by linking between commercial parties having transaction partners who commit fraud, they do not report to the state but they have taken the value of 23 pph on the commercial side and when the commercial party wanting to report a pph 25 will have an impact on paying taxes to countries that cannot be credited. But according to the researcher's view it can be minimized when instilling love, because with love, accounting related to tax reporting and income tax 23 will have an impact on their ethics and morals in reporting and paying taxes. So with a sense of love can be minimized the occurrence of fraud that can be troubling commercial parties.